Язык и датировка Фирлеевского списка Первого Литовского Статута - Булыка, А.; Рауделюнас, В. (Kalbotyra, 1976)
During the years of its validity (1529–1564) the First Lithuanian Statute wasn’t reprinted and only manuscript copies were spread. 11 copies are known this moment, 4 of which are written in the old Byelorussian language, 3, in Polish, and 4, in Latin. The copy of Firlej together with the copies of Dzialinskij, Zamoiskij and Stuck, made up one group of copies, written in the old Byelorussian language.The copy of Firlej is preserved in Warsaw in the National library of the Polish People’s Republic (sign. – Baw. 952). It is a manuscript book of the quarterly size (20.8 × 15.8 cm) having 266 pages. The manuscript is knitted in (bound) wood covers, covered with even brown leather. The text of the manuscript is written by one author, except for the first 14 pages.The copy of Firlej is written in the typical Byelorussian quick writing of the second fourth of the 16th c. which in the old Grand Duchy of Lithuania was used for businesslike writing. The copy of Firlej consists of the text of the Statute and the register of titles of its articles. Some of the Chapters of the register have less articles than in the original text of the Statute. Though the copy of the text is exact, some spelling mistakes happen to occur, separate words are omitted at all or their places are changed. Nevertheless, some of the articles of the copies are more clearly formulated and haven’t any mistakes, which happen in other copies frequently. The data of paleography, language and philigranalogy show that the copy of Firlej came from the Lithuanian-Byelorussian frontier lands during the years of passing of the First Statute (1529) and its first year of validity. In the 17th c. the copy got to the Ukraine and belonged to clergy or other persons close to clergy. Virtually many researchers couldn’t appreciate scientifically the copy of Firlej, because they judged about it not according to the manuscript, but according to the printed publication full of mistakes. According to its text, the copy belongs to the group of the First Statute copies of the short editorship and is closest to its original. Qualities of the copy of Firlej enable to affirm that it should be assumed as a basis for the future edition of the First Statute. Besides, the edition should be academic and include all 11 copies of the Statute known by this time.